2020
DOI: 10.1177/1066896920921238
|View full text |Cite
|
Sign up to set email alerts
|

Intrasinusoidal HHV8-EBV–Positive Large B-Cell Lymphoma With Features of Germinotropic Lymphoproliferative Disorder

Abstract: Germinotropic lymphoproliferative disorder (GLPD) is a poorly characterized lymphoproliferative entity, recently included in the World Health Organization classification of hematolymphoid neoplasms. The histological pattern of this disease comprises monotypic plasmablasts that involve the germinal centers of the lymphoid follicles (germinotrophism), forming confluent aggregates positive for both human herpes virus type 8 (HHV8) and Epstein-Barr virus. Currently, after 17 years of its first description, only 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, the atypical cells were predominantly sinusoidal and paracortical, only partially involving follicles (without appearing focused in germinal centers) and without interfollicular polytypic plasmacytosis. Given the pattern and lack of light chain expression, the panel felt the findings were most in keeping with focal involvement by ECPEL; however, some authors have raised consideration that additional patterns may exist for GLPD [ 18 21 ].…”
Section: Extracavitary Primary Effusion Lymphoma (Ecpel)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the atypical cells were predominantly sinusoidal and paracortical, only partially involving follicles (without appearing focused in germinal centers) and without interfollicular polytypic plasmacytosis. Given the pattern and lack of light chain expression, the panel felt the findings were most in keeping with focal involvement by ECPEL; however, some authors have raised consideration that additional patterns may exist for GLPD [ 18 21 ].…”
Section: Extracavitary Primary Effusion Lymphoma (Ecpel)mentioning
confidence: 99%
“…Given the overlap in cytomorphology and immunophenotype, the morphologic pattern is often the most useful diagnostic feature in GLPD: general retention of nodal architecture and involvement of germinal centers by medium to large plasmablastic cells [ 1 ]. When alternative patterns have been reported, such as sinusoidal, mantle, and interfollicular involvement, this is usually in addition to germinal center involvement [ 8 , 18 20 ], although not always [ 21 ]. A recent review [ 19 ] found that interfollicular polytypic plasmacytosis was a common feature in GLPD (~37%), which has also been reported as a prominent finding by others [ 18 , 22 ].…”
Section: Extracavitary Primary Effusion Lymphoma (Ecpel)mentioning
confidence: 99%
“…In the second case, we found the entire spectrum of HHV8‐related disorders (MCD, GLPD, and PEL) coexisting in the same lymph node, underlining the variability, the overlap and the possible evolution among these entities. Cases with clinicopathological features of MCD enriched for plasmablastic aggregates and GLPD have been reported, suggesting an overlap with MCD and GLPD in a subset of cases 25,34 . Although GLPD progressing to lymphoma has been reported in HIV‐positive and HIV‐negative patients, 29 definitive association and evolution from MCD to GLPD or EC‐PEL is still not recognised 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Cases with clinicopathological features of MCD enriched for plasmablastic aggregates and GLPD have been reported, suggesting an overlap with MCD and GLPD in a subset of cases. 25 , 34 Although GLPD progressing to lymphoma has been reported in HIV‐positive and HIV‐negative patients, 29 definitive association and evolution from MCD to GLPD or EC‐PEL is still not recognised. 46 In our case we were able to demonstrate a clonal relationship between the atypical large cells in the germinal centres and in the sinuses from the same lymph node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation